Raman spectroscopy-based identification of toxoid vaccine products. (December 2018) - Silge, Anja; Bocklitz, Thomas; Becker, Bjoern; Matheis, Walter; Popp, Juergen; Bekeredjian-Ding, Isabelle
Abstract Vaccines are complex biomedicines. Manufacturing is time consuming and requires a high level of quality control (QC) to guarantee consistent safety and potency. An increasing global demand has led to the need to reduce time and cost of manufacturing. The evolving concepts for QC and the upcoming threat of falsification of biomedicines define a new need for methods that allow the fast and reliable identification of vaccines. Raman spectroscopy is a non-destructive technology already established in QC of classical medicines. We hypothesized that Raman spectroscopy could be used for identification and differentiation of vaccine products. Raman maps obtained from air-dried samples of combination vaccines containing antigens from tetanus, diphtheria and pertussis (DTaP vaccines) were summarized to compile product-specific Raman signatures. Sources of technical variance were emphasized to evaluate the robustness and sensitivity in downstream data analysis. The data management approach corrects for spatial inhomogeneities in the dried sample while offering a proper representation of the original samples inherent chemical signature. Reproducibility of the identification was validated by a leave-one-replicate-out cross-validation. The results highlighted the high specificity and sensitivity of Raman measurements in identifying DTaP vaccine products. The results pave the way for further exploitation of the Raman technology for identification of vaccines in batch release and cases of suspected falsification. Quality control: Rapid and reliable vaccine analysis A light-based identification method offers a fast, reliable and non-destructive method to analyze vaccines. Using vaccines for tetanus, diphtheria, and pertussis, a German research team led by the Paul Ehrlich Institute and University of Jena and Leibniz-IPHT showed that Raman spectroscopy — which identifies substances based on how they scatter laser light — is able to identify distinctive signatures of vaccines. In their experiments, Raman spectroscopy was sensitive enough to detect subtle differences in vaccine formulation, such as the specific combination of vaccine and adjuvant components. However, a data analytics technique was required to correct for sample quality variation caused by their preparation. Raman spectroscopy already sees use in classical medicines, and its application to vaccines could help to reduce the time and cost of quality control while benefitting the unmet need for rapid analysis of vaccine quality and identity.